Pengaruh Sifat Shiddiq, Amanah, Fathanah, Tabligh & Istiqamah terhadap Resiliensi Mahasiswa Wirausaha P2MW - Astuti, Sannis Hening; Kusumastuti, Wanodya; Esterina, Merriam (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the effect of the characteristics of siddiq, amanah, fathanah, tabligh and istiqamah on the resilience of P2MW entrepreneurial students. The variables in this study are siddiq, amanah, fathanah, tabligh and istiqamah as independent variables and resilience as the dependent variable. The research method used is quantitative, with a purposive sampling technique. The subjects of the study were students who passed the Student Entrepreneurship Development Program funding in 2022-2024. The data collection instrument used the SAFT+I questionnaire and resilience, the research data was analyzed using multiple linear regression analysis with the help of the IBM SPSS program. The results of the simultaneous F test showed that the characteristics of siddiq, amanah, fathanah, tabligh and istiqamah had an effect on the resilience of P2MW entrepreneurial students, while the results of the t test stated that partially the amanah and istiqamah variables had a positive and significant effect on the resilience of P2MW entrepreneurial students, while the tabligh variable had a positive and insignificant effect, and the siddiq and fathanah variables did not have an effect on the resilience of entrepreneurial students.